Patchy Alopecia in a Patient with Rheumatoid Arthritis: A Practical Application of Trichoscopy - Ahmad Vafaeian; Elham Taghizadeh; Maryam Daneshpazhooh; Hamidreza Mahmoudi (Karger Publishers, 2021)
Trichoscopy is an efficient, convenient, and accurate diagnostic dermatological procedure which is widely used in the examination of patients with skin diseases. Herein, we report a 56-year-old woman with a long-term history of rheumatoid arthritis complaining of pruritic patchy alopecia on her scalp who was referred for biopsy to exclude cutaneous lupus erythematosus. Taking advantage of trichoscopy, we were able to quickly diagnose tinea capitis. Following administration of the proper treatment the disease resolved completely.